Where are Socially-Engaged Scholarship Articles Published in the Scopus Database? - Sirisathitkul, Chitnarong (Area Based Development Research Journal, 2021)
Area-based research for development, art and cultural conservation, and academic service by every university have greatly contributed to community and society as a whole. However, the potential of presenting such works in academic journals is often overlooked. This article encourages more publications of sociallyengaged scholarship from Thai universities in international journals. Interesting journal titles with some recent publications from the Scopus database are exemplified according to the journal category. The socially-engaged scholarship is interdisciplinary but the discipline-oriented publication is recommended as an alternative strategy for attracting attentions of journals from different categories including management, agriculture, environment, education and cultural studies. For targeted multidisciplinary journals, it is fitting that sustainability, an important keywords in socially-engaged scholarship, is the theme. The opportunities of publishing academic service, art and cultural conservation, as well as area-based research for development in journals with a wide or unlimited scope are also presented.